Impact of Multiple Intelligence-Based Activities (MIBAs) on the Improvement of Male and Female EFL Students’ Aural-Oral Performance - Lotfi-Khajouei, Marjan; Baharlooei , Roya; Salehi, Hadi; Tabatabaei, Omid (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
This study aimed at investigating the impact of Gardner’s multiple intelligence-based activities (MIBAs) to improve the aural-oral performance of EFL students. Therefore, 60 Iranian intermediate EFL university students were selected. They were divided into two equal groups of experimental. The experimental group was taught through some activities designed on the basis of Gardner’s definition of eight intelligence types, while a traditional method including some activities like repetition drills, memorization, etc. was employed for the control group. The findings revealed that the use of MIBAs had a significant effect on EFL students’ aural-oral performance and the experimental group outperformed the control group; however, there was not a significant difference between male and female students in terms of their improvement. The results of the study may offer some implications for the fields of teaching, material preparation, and curriculum designing. This study can be replicated in different settings, with different skills and sub-skills.